Correlation between Thyroid-related Hormones and Preeclampsia - Al-Naqeeb, Asmehan (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: In order to highlight the TSH and thyroid hormones levels in preeclamptic and healthy pregnantwomen.Methodology: Ninety patients with preeclampsia were divided into two groups according to the severity ofdisease; those with mild disease (37 patients) and those with a severe form (53 patients). A separate group of 30normal women were included as a normal control group. Venus blood samples were collected from all groupsand the serum was obtained for hormone analysis by ELISA test. Results are expressed using SPSS for windowversion 11.0.Results: Mean serum TSH levels were significantly increased in both of mild and severe preeclampsia comparedwith normal pregnancy, and T3 serum level showed a significant increase in mild and severe preeclampticwomen compared with healthy pregnant ones without concomitant change in T4 in each group of preeclampticwomen compared to normal pregnancy.Recommendations: Studying the relationship between preeclampsia and its effect on the secretion of pituitarygland to ADH, studying the role of adrenal gland, hypothalamus and their secretions in preeclampsia.